Choices of Stent and Cerebral Protection in the Ongoing ACST-2 Trial: A Descriptive Study. (May 2017) - de Waard, D.D.; Halliday, A.; de Borst, G.J.; Bulbulia, R.; Huibers, A.; Casana, R.; Bonati, L.H.; Tolva, V.; ,
Abstract : Objective/Background: Several plaque and lesion characteristics have been associated with an increased risk for procedural stroke during or shortly after carotid artery stenting (CAS). While technical advancements in stent design and cerebral protection devices (CPD) may help reduce the procedural stroke risk, and anatomy remains important, tailoring stenting procedures according to plaque and lesion characteristics might be a useful strategy in reducing stroke associated with CAS. In this descriptive report of the ongoing Asymptomatic Carotid Surgery Trial-2 (ACST-2), it was assessed whether choice for stent and use or type of CPD was influenced by plaque and lesion characteristics. Methods: Trial patients who underwent CAS between 2008 and 2015 were included in this study. Chi-square statistics were used to study the effects of plaque echolucency, ipsilateral preocclusive disease (90–99%), and contralateral high-grade stenosis (>50%) or occlusion of the carotid artery on interventionalists' choice for stent and CPD. Differences in treatment preference between specialties were also analysed. Results: In this study, 831 patients from 88 ACST-2 centres were included. Almost all procedures were performed by either interventional radiologists (50%) or vascular surgeons (45%). Plaque echolucency, ipsilateral preocclusive disease (90–99%), and significant contralateral stenosis (>50%) or occlusion did not affect the choice of stent or either the use of cerebral protection and type of CPD employed (i.e., filter/flow reversal). Vascular surgeons used a CPD significantly more often than interventional radiologists (98.6% vs. 76.3%; p < .001), but this choice did not appear to be dependent on patient characteristics. Conclusion: In ACST-2, plaque characteristics and severity of stenosis did not primarily determine interventionalists' choice of stent or use or type of CPD, suggesting that other factors, such as vascular anatomy or personal and centre preference, may be more important. Stent and CPD use was highly heterogeneous among participating European centres.